2015
DOI: 10.1371/journal.pone.0124013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lysyl Oxidase Inhibition on Angiotensin II-Induced Arterial Hypertension, Remodeling, and Stiffness

Abstract: It is well accepted that angiotensin II (Ang II) induces altered vascular stiffness through responses including both structural and material remodeling. Concurrent with remodeling is the induction of the enzyme lysyl oxidase (LOX) through which ECM proteins are cross-linked. The study objective was to determine the effect of LOX mediated cross-linking on vascular mechanical properties. Three-month old mice were chronically treated with Ang II with or without the LOX blocker, β -aminopropionitrile (BAPN), for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
2
27
0
2
Order By: Relevance
“…Previous studies reported increased LOX mRNA or activity levels in some models of hypertension (19,43,48). We confirm these observations and demonstrate that the upregulation of vascular LOX protein levels observed in SHR and Ang II-infused mice relies, at least in part, on the hemodynamic effects induced by high blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies reported increased LOX mRNA or activity levels in some models of hypertension (19,43,48). We confirm these observations and demonstrate that the upregulation of vascular LOX protein levels observed in SHR and Ang II-infused mice relies, at least in part, on the hemodynamic effects induced by high blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…LOX has been shown to induce an age‐dependent disturbance of diastolic function and aggravates angiotensin II (Ang II)‐induced hypertrophy . In addition, inhibition of LOX by BAPN attenuated the Ang II‐induced arterial hypertension and adventitial thickness . Besides, BAPN attenuated volume overload‐induced increase in cardiac stress, levels of collagen I and III, and cardiac dysfunction in the heart failure model rats induced by volume overload following aortocaval fistula (ACF) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, while it has been shown that the downregulation of LOX contributes to the aortic stiffening in an obesity mouse model (Chen et al., 2013), other studies have shown that inhibition of LOX attenuated the angiotensin II induced aortic stiffening (Eberson et al., 2015). In addition, as evidence showed that genetic deletion or functional deficiency of LOX causes aortic wall destruction and leads to aortic stiffening (Lee et al., 2016; Maki et al., 2002; Staiculescu et al., 2017), a smooth muscle cell‐specific overexpression of LOX in a mouse model has been shown to induces arterial stiffness (Martinez‐Revelles et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate an essential role of LOX in maintaining the tensile and elastic features of blood vessels. Studies of the role of LOX in hypertensive aortic stiffening, however, have produced inconsistent results (Chen et al., 2013; Eberson et al., 2015). …”
Section: Introductionmentioning
confidence: 99%